Examining the possible causal relationship between lung function, COPD and Alzheimer's disease: a Mendelian randomisation study. Issue 1 (7th July 2021) - Higbee, Daniel; Granell, Raquel; Walton, Esther; Korologou-Linden, Roxanna; Davey Smith, George; Dodd, James
Abstract : Rationale: Large retrospective case-control studies have reported an association between chronic obstructive pulmonary disease (COPD), reduced lung function and an increased risk of Alzheimer's disease. However, it remains unclear if these diseases are causally linked, or due to shared risk factors. Conventional observational epidemiology suffers from unmeasured confounding and reverse causation. Additional analyses addressing causality are required. Objectives: To examine a causal relationship between COPD, lung function and Alzheimer's disease. Methods: Using two-sample Mendelian randomisation, we used single nucleotide polymorphisms (SNPs) identified in a genome wide association study (GWAS) for lung function as instrumental variables (exposure). Additionally, we used SNPs discovered in a GWAS for COPD in those with moderate to very severe obstruction. The effect of these SNPs on Alzheimer's disease (outcome) was taken from a GWAS based on a sample of 24 807 patients and 55 058 controls. Results: We found minimal evidence for an effect of either lung function (OR: 1.02 per SD; 95% CI 0.91 to 1.13; p value 0.68) or liability for COPD on Alzheimer's disease (OR: 0.97 per SD; 95% CI 0.92 to 1.03; p value 0.40). Conclusion: Neither reduced lung function nor liability COPD are likely to be causally associated with an increased risk of Alzheimer's, any observed association is likely due to unmeasured confounding. Scientific attention and health prevention policy may be better focused on overlapping risk factors, rather than attempts to reduce risk of Alzheimer's disease by targeting impaired lung function or COPD directly.